(untitled) (World of finance, 2025)
Introduction. Sustainable development and urban transformations play an important role in the context of innovation, as modern cities are the main centers of technological progress, economic activity and demographic challenges. The introduction of innovations into the urban environment allows to improve the quality of life, ensure the efficiency of infrastructure and respond to the challenges of climate change, energy efficiency and social integration. The purpose of the article is to determine the main components of the development of the high-tech innovation sphere in Ukraine in the context of sustainable development and urbanism. Results. The presented work analyzes the features of the development of the high-tech innovation sphere, determines its essence and main components. The essence of urbanism and sustainable development in combination with the features of the functioning of the hightech innovation sphere is also determined. Methodological provisions on the development of the high-tech sphere in the context of sustainable development and urbanism are formed. Conclusions. The development of the high-tech innovation sector in Ukraine in the context of sustainable development and urbanism is a strategically important direction for ensuring competitiveness, economic sustainability and improving the quality of life of the population. The analysis showed that innovative technologies and infrastructure solutions can become the basis for the transformation of the urban environment, reducing socio-economic inequality and increasing the efficiency of resource use. Therefore, for the successful development of the high-tech innovation sector, Ukraine needs to intensify inter-sectoral cooperation, stimulate investments in scientific and technological research, modernize infrastructure and introduce mechanisms to support innovation activities. These measures will create the prerequisites for the integration of technologies into urban space, ensure sustainable socio-economic development and improve the quality of life of the population in the conditions of modern urbanization and digitalization.